Formal Rules and Informal Institutions of Their Application in the Russian Economic Practice - ПанеяхЭлла Львовна (Journal of Economic Sociology, 2010)
The paper is an attempt to apply the institutional theory of D. North to the description of the practices, formed in Russian economy around the inflorescent of the economic legislation. The main attention is given to the problem of formal rule observance and transaction costs of this observance. The research is based on 60 interviews with small entrepreneurs and self-employed in Khabarovsk, Novosibirsk and Saint-Petersburg, including those working in the informal sector only in 1999-2001 and 100 interviews with entrepreneurs, self-employed and housekeepers in Moscow, Khabarovsk, Novosibirsk and Saint-Petersburg in 2000- 2001.